School-Based 4-H Programming: Working with Partners Effectively - Vanessa Spero (EDIS, 2019)
Partnerships open a world of possibilities. Partnerships provide an opportunity for multiple organizations to address community challenges while benefiting at the same time through shared resources, funding, personnel, and expertise. Desiring to partner with a school-based site is beneficial, but not always easy to implement. Being professional in your collaboration, prepared in your assessment, and intentional about your needs are ways to increase the likelihood of a successful partnership. This 4-page publication of the UF/IFAS Florida 4-H Youth Development program offers tips and strategies to build healthy, mutually beneficial partnerships in your program. Written by Vanessa Spero-Swingle. https://edis.ifas.ufl.edu/4h399